AB0179 Bone mineral density measurements in obese patients. (1st June 2001) - Atalay, A; Arslan, S; Çeliker, R
Abstract : Background: Obese patients are prone to develop many medical conditions, including musculoskeletal problems. Obesity seems to have a protective effect on bone explained by metabolic mechanisms. Further studies will lead to better understanding of the impact of the weight on bone mineral density (BMD) measurements. Objectives: The aim of this study was to evaluate the relationship between obesity and lumbar and femoral BMD measurements. Methods: The study population consisted of 71 female patients from our outpatient clinics. Clinical assessment and anthropometric measurements (height, weight, abdominal circumference, waist circumference, triceps skinfold thickness) were performed by the same physician. Body mass index (BMI) was calculated as kg/m 2 and cut-off points defined by World Health Organisation (WHO) were used to identify obesity. Cut-off values are as follows: 18.5–24.99: normal, 25.0–29.99 grade1 overweight, 30.0–39.99 grade 2 overweight, > = 40.0 grade 3 overweight. Lumbar and femoral BMD measurements were obtained using dual energy X-ray absorptiometry (DEXA) (Hologic QDR 4500A). Subjects were divided into two groups: subjects with BMI < = 29.9 and subjects > 29.9, and statistical analysis were carried out accordingly. p < 0.05 was considered to be statistically significant. Results: The mean age of the subjects was 52.96 ± 10.87 years (range:25–78 years) and mean BMI was 31.40 ± 5.62 (range: 21.91–47.27). According to WHO criteria: 12 subjects (16.9%) were within the normal range, 16 subjects (22.5%) were grade 1 obese, 39 subjects (54.9%) grade 2 obese and 4 subjects (5.6%) grade 3 obese. BMD measurements in all areas examined (lumbar total, L1, L2, L3, L4, intertrochanteric, neck, trochanteric and femoral total) were correlated with anthropometric measurements. BMI was positively correlated with lumbar and femoral bone mineral density measurements in all regions evaluated. BMD measurements in all areas examined (lumbar total, L1, L2, L3, L4, intertrochanteric, neck, trochanteric and femoral total) were compared according to two groups (BMI < = 29.9, BMI > 29.9). In all areas there was a significant difference between the two groups in favour of the obese group. Conclusion: In accordance with the previous studies, our study indicates the positive relationship between obesity and bone mineral density measurements. Reference: World Health Organization. Physical status: The use and interpretation of anthropometry. Report of a WHO expert committee . Geneva: World Health Organization, 1995